Tracing site-specific isotopic signatures along a Blue Tit Cyanistes caeruleus food chain - Charmantier, Anne; Blondel, Jacques; Perret, Philippe; Harmelin-Vivien, Mireille (IBIS, 2014)
Food chains culminating with temperate insectivorous passerines are well described, yet whether trophic webs can be site-specific remains a largely unexplored question. In the case of site- or habitat-specificity of food webs, stable isotope signatures of bird feathers may enable assignment of unmarked individuals to a site or a habitat of origin. We address this question in landscapes that include contrasting forest habitat patches with either deciduous Downy Oak Quercus humilis or evergreen Holm Oak Quercus ilex as dominant tree species. First, we examine the spatial variation across habitats and sites in the stable isotope ratios of carbon (C-13) and nitrogen (N-15) along the oak leaf-Tortrix moth Tortrix viridana caterpillar-Blue Tit Cyanistes caeruleus food chain. Secondly, we assess whether the isotopic signatures allow for correct assignment of individual birds to their site or habitat of origin. At the scale of the landscape, stable isotope values enabled identification of the different components of the Blue Tit food chain: from oak leaves to Blue Tit nestlings and yearling birds. However, isotopic signatures were site-specific (i.e. geographical) more than habitat-specific (i.e. deciduous vs. evergreen oaks). Discriminant analyses correctly assigned 85% of nestlings and 83% of resident yearling birds, indicating a pronounced effect of site on Blue Tit feather isotopic signatures. We thereby demonstrate that isotopes reflect a stronger association of locally born birds to the local features of their habitat than that of un-ringed yearling birds, whose plumage may have grown while in a wider geographical area. This study provides evidence of site-specific isotopic signatures from oak leaves to Blue Tit feathers at a fine spatial scale.
The following values have no corresponding Zotero field: pub-location: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA publisher: WILEY-BLACKWELL
Keywords: environment heterogeneity; habitat-specific isotopic signature; natal dispersal; trophic ecology

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC; Blondel, Jacques; Thomas, DonaldW (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM.; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC.; Blondel, Jacques; Thomas, DonaldW. (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction